An experimental and modeling study on the penetration of spilled oil into thawing frozen soil. Issue 12 (9th November 2022) - Qu, Zhaonian; An, Chunjiang; Mei, Zhu; Yue, Rengyu; Zhao, Shan; Feng, Qi; Cai, Mengfan; Wen, Jiyuan
Abstract : This study reveals the features of oil penetration behavior and distribution patterns in thawing frozen soil under different conditions, which can help develop rapid response measures in cold regions. Abstract : Oil spills are significant environmental accidents that have significant impacts on environmental and ecological health. Spill pollution in the cold regions may pose a particular challenge. To achieve a fast response, the oil transport mode such as penetration should be well understood. In this study, the oil penetration behavior in thawing frozen soil at different temperatures and water contents were investigated. The results showed the penetration behavior of spilled oil in the thawing frozen soil and the influence of salinity level. The modified Green-Ampt model could simulate the penetration process well especially with high water content, relatively cold temperature, and slow thawing rate. This study reveals the new features of oil penetration behavior and distribution patterns in thawing frozen soil under different conditions. Hence, it is of significant importance to support the rapid response measures and reduce the contamination of oil spill accidents in cold regions.